Agatha Raisin. [videorecording (DVD)] Series one - Beaton, M. C.; Jensen, Ashley; Horne, Mathew, 1978-; Wix, Katy, 1979- (Acorn, 2016)
Based on the beloved character created by M.C. Beaton. Agatha, public relations specialist, moves from London to the small village of Carsley, hoping for a quieter, simpler life. She soon finds her dreams dashed when she becomes a murder suspect after entering a quiche-making competition.